Trade negotiations in the Tokyo Round : a quantitative assessment - Cline, William R.; Cline, William R. (Washington : Brookings Institution, 1978)
In this book, the author seeks to quantify the prospective economic effects of trade liberalization in the Tokyo Round.
Includes bibliographical references and index.
ijb, 15/01/2019
Loans
Keywords: Tariff; Non-tariff trade barriers